2012
DOI: 10.14417/ap.479
|View full text |Cite
|
Sign up to set email alerts
|

Reminiscência enquanto ferramenta de trabalho com idosos: Vantagens e limitações

Abstract: O objectivo deste artigo é analisar a importância da reminiscência enquanto estratégia terapêutica junto de idosos. Explora-se o conceito de reminiscência tal como decorre no quotidiano e analisa-se o seu surgimento como estratégia de trabalho com idosos, considerando os seus principais âmbitos de intervenção, desde moldes preventivos, como a adaptação à institucionalização, até níveis remediativos, como a estimulação do funcionamento cognitivo em quadros demenciais. Por fim, listam-se aquelas que se considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
11
0
2
Order By: Relevance
“…Reminiscence interventions is based on the expertise the person has on his/her own life, which oneself knows very well, without the need of learning new abilities (Gonçalves et al, 2008) and can be used with early memories that remain relatively intact (Cotelli et al, 2012). Reminiscence is centred on the person's preserved abilities rather than focusing on the level of impairment caused by the disease (Cotelli et al, 2012;Gonçalves et al, 2008;O'Shea et al, 2011) and this is ought to be optimized in future investigations. Bearing in mind the therapeutic benefits of reminiscence in the emotional status, this study also showed a decrease of depressive symptoms that was statistically significant when comparing self reported depression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reminiscence interventions is based on the expertise the person has on his/her own life, which oneself knows very well, without the need of learning new abilities (Gonçalves et al, 2008) and can be used with early memories that remain relatively intact (Cotelli et al, 2012). Reminiscence is centred on the person's preserved abilities rather than focusing on the level of impairment caused by the disease (Cotelli et al, 2012;Gonçalves et al, 2008;O'Shea et al, 2011) and this is ought to be optimized in future investigations. Bearing in mind the therapeutic benefits of reminiscence in the emotional status, this study also showed a decrease of depressive symptoms that was statistically significant when comparing self reported depression.…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent this bias, the literature alerts to the need of multicentre randomized control trials with larger samples, multiple settings, and diverse therapists following a common intervention protocol (Subramaniam et al, 2014). The absence of consensual structured models for intervention is also seen as a methodological obstacle to effective reminiscence therapy and so it would be useful to establish in the future which objectives, intervention strategies and assessment methodologies are contributing to the available flimsy results (Gonçalves et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since no RT program has yet been developed that can be replicated in Portuguese settings, and considering that the lack of consensual structured intervention models may explain the methodological weaknesses that limit the analysis of the effectiveness of RT programs (Gonçalves, Albuquerque, & Martín, 2008;Cotelli et al, 2012), it was important to deve-lop and validate a program of this nature. The Medical Research Council (Craig et al, 2008) introduced the concept of complex intervention, describing it as a number of interactions between components within the experimental and control interventions, the number and difficulty of behaviors required by those delivering or receiving the intervention, a number of groups or organizational levels targeted by the intervention, the variability of outcomes, and the degree of flexibility or tailoring of the intervention permitted.…”
Section: Introductionmentioning
confidence: 99%